PENGARUH AGRESIVITAS PAJAK TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Arfiyanto, Rizky; Ardiyanto, Moh Didik (Diponegoro Journal of Accounting, 2017)
This study aims to examine the effect of tax aggressiveness on corporate social responsibility disclosure. The dependent variable used in this study is the disclosure of social responsibility. While the independent variable in this study is the tax aggressiveness measured using the proxy Effective Tax Rates (ETR). This study uses four control variable; include capiral intensity, market to book ratio, return on asset (ROA), dan size.This study is a replication of the study by Lanis and Richardson (2013) and using 196 manufacturing companies that listed on the Indonesia Stock Exchange in the perioed 2013-2016 as the sample. The sample is chosen by purposive sampling method and there are 24 data outlier. The company that meet the criteria of this research are 168 companies. Data were analyzed using ordinary least square regression analysis model. The study indicate that tax aggressiveness has a positive and significant impact on the disclosure of Corporate Social Responsibility. The study indicate that the higher the level of tax aggressiveness of a company, the greater the disclosure of Corporate Social Responsibility. So this study justify the theory of legitimacy.